Hubungan Mutu Pelayanan Kesehatan dan Kepuasan Pasien BPJS Rawat Jalan Puskesmas Kejaksan Kota Cirebon - karina utami (Poltekkes Kemenkes Yogyakarta, 2025)
This research was conducted at the Kejaksan Public Health Center (Puskesmas Kejaksan) in Cirebon City, with a total sample of 40 respondents in August 2025. The samples were selected using the total random sampling technique, based on Roscoe’s opinion in Research Methods for Business (1982:253) as cited in Sugiyono (2020:90), which states that the minimum sample size for research should be 30 samples.This study was based on preliminary observations and interviews with several patients, which revealed that some were still dissatisfied with the services provided by Puskesmas Kejaksan, Cirebon City.The purpose of this study was to determine whether there is a relationship between the quality of health services and the satisfaction of BPJS outpatient patients at Puskesmas Kejaksan, Cirebon City. Data were collected through observation, questionnaires, and literature study, while data analysis employed validity tests, reliability tests, and simple regression analysis.The results of the data analysis showed that the variables of health service quality and patient satisfaction had a validity test value lower than the r-table value (0.004), and using the Chi-Square Test, it was found that Ho was rejected and H1 was accepted. Therefore, there is a significant relationship between the quality of health services and the satisfaction of BPJS patients at Puskesmas Kejaksan, Cirebon City. It is thus necessary to improve the quality of health services to further enhance patient satisfaction among those seeking treatment at Puskesmas Kejaksan, Cirebon City